2016
DOI: 10.1038/npp.2016.192
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Electrophysiological Evidence of Reward and Punishment-Based Learning and Psychotic Experiences and Social Anhedonia in At-Risk Groups

Abstract: Both positive psychotic symptoms and anhedonia are associated with striatal functioning, but few studies have linked risk for psychotic disorders to a neural measure evoked during a striatal dopamine-related reward and punishment-based learning task, such as a reversal learning task (RLT; Cools et al, 2009). The feedback-related negativity (FRN) is a neural response that in part reflects striatal dopamine functioning. We recorded EEG during the RLT in three groups: (a) people with psychotic experiences (PE; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
(45 reference statements)
3
11
0
Order By: Relevance
“…Medication use was not significantly correlated with resting-state functional connectivity, and we found a similar pattern of results if we excluded the people using medication. Previous striatum-related behavioral (Karcher, Martin, & Kerns, 2015) and electroencephalographic (Karcher, Bartholow, Martin, & Kerns, 2017) studies comparing psychosis risk and control groups had found large effect size differences (ds = 1.36 and 1.14, respectively; power to detect these effect sizes in the present study = .98 and .92; the present study had .80 power to detect an effect size of 0.95; power analyses were conducted using G*Power 3.1; Faul, Erdfelder, Buchner, & Lang, 2009). The samples in the present study were not shared with previous studies (Karcher et al, 2015;Karcher et al, 2017).…”
Section: Participantsmentioning
confidence: 99%
“…Medication use was not significantly correlated with resting-state functional connectivity, and we found a similar pattern of results if we excluded the people using medication. Previous striatum-related behavioral (Karcher, Martin, & Kerns, 2015) and electroencephalographic (Karcher, Bartholow, Martin, & Kerns, 2017) studies comparing psychosis risk and control groups had found large effect size differences (ds = 1.36 and 1.14, respectively; power to detect these effect sizes in the present study = .98 and .92; the present study had .80 power to detect an effect size of 0.95; power analyses were conducted using G*Power 3.1; Faul, Erdfelder, Buchner, & Lang, 2009). The samples in the present study were not shared with previous studies (Karcher et al, 2015;Karcher et al, 2017).…”
Section: Participantsmentioning
confidence: 99%
“…The current study involved antipsychotic medication-naive people with increased risk for psychosis (i.e., psychosis risk group; n = 20 with useable imaging data; n = 21 with behavioral data) and a comparison group not at increased risk for psychosis (n = 20). Our previous EEG study comparing psychosis risk and a nonrisk comparison group on the same RLT found a large neural effect size difference between groups, d = 1.14 [16]. In the current study, given our sample size, our power to detect that same effect size was 0.94.…”
Section: Methods and Materials Participantsmentioning
confidence: 48%
“…Participants completed a task previously found to activate the striatum, a RLT [16,17,32]. In general, on RLTs, participants first learn that one stimulus is rewarded and that a different second stimulus is punished.…”
Section: Reversal-learning Task (Rlt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Anhedonia is defined as reduced interest or pleasure previously rewarding activities, part of a spectrum of reward circuit abnormalities ( Der-Avakian and Markou, 2012 ). Convergent studies implicated the dysfunction of reward brain system in the neurobiology of anhedonia ( Auerbach et al, 2017 ; Karcher et al, 2017 ). Indeed, behavioral studies have revealed the abnormality during reward-related processing in depression ( Rizvi et al, 2018 ), displayed several types such as reward response bias, impaired reward learning ability and increased risk avoidance ( Smoski et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%